TEACHERS' PROBLEMS IN IMPLEMENTING THE INDEPENDENT LEARNING CURRICULUM IN GRADE V STUDENTS OF SDIT INSAN GEMILANG SIGI - Ayu Lestari; Askar Askar; Elya Elya (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Roblematics is an obstacle or problem that still creates a problem that cannot yet be solved, so that achieving the goal becomes hampered and not optimal. The purpose of this study is to determine the Implementation of the Independent Learning Curriculum and to determine the teacher's efforts in overcoming the problems of the Independent Learning Curriculum in class V SDIT Insan Gemilang Sigi.This thesis is entitled